G SUIT FOR EDUCATION AS AN ENVIRONMENT FOR STUDENTS OF EDUCATIONAL PRACTICES - Glazunova, О.Г.; Kuzminska, О.Г.; Voloshyna, Т.В.; Sayapina, Т.П.; Korolchuk, В.І (Journal of Information Technologies in Education (ITE), 2017)
Materials article analyzes the opportunities and benefits of using cloud services G Suite (Google Apps) during the practical training of students. In the course of the study, an e-environment based on G Suit for Education was developed and its use for effective organization of information technology practice training. A model of e-learning environment for organizing group project work in Google Classroom-based training has been built. The design methodology is grounded as one of the most effective for the organization of educational practice in information technologies. The stages of realization of the project task during the educational practice, as well as the tools, the achieved competence, features of the activity of teachers and students at each stage are researched.Examples of tasks, resources and services that were used to achieve project results are given.The implementation of individual project implementation phases in the Google Classroom-based electronic environment has been demonstrated, in particular, project planning, adding new services in the electronic environment, collaborative work with documents, portfolio elements, student reflection. The results of the survey of students on the organization of educational practice using the method of projects and the e-environment based on the use of cloud services G Suite (Google Apps)are analyzed.